(3GdJhLjg GdJQHhj ddeQGgb hCKQg Ydi YdGbJg HCSQJgs - (3MGhj, eMeOs ((3HjQhJs (3OGQ GdgGOjs, 2008)
(3GdgOa ef gPg GdOQGSI gh EdbGA GdVhA Ydi MjGI GdeQGgb GdGLJeGYjI hGdJQHhjI hGdYdGbI Hjfg hHjf GdeQTO GdJQHhj Ch ef Sha jCNP HjOg Edi WQjb GdCeGf hjhUdg Edi eG jHZj GdhUhd Edjg hab GSJYOGOGJg hbOQGJg(B. (3haQVjI GdHMK gj Cfg cdeG cGf GdJhLjg GdJQHhj ddeQGgb jSjQ HGJLGg Sdje cdeG cGf GSJYOGO GdeQGgb dCf jLO faSg aj GdecGf GdPj JSeM dg EecGfjGJg HGdMUhd Ydjg Ch JUhjH GdeSGQ GdPj jSjQ Hg GdeQGgb, Cj Cf Sdhc GdeQGgb GdJQHhj jJMOO ef NdGd Yed GdeQTO Ch GdehLg GdJQHhj(B. (3hjJVef ehVhY GdHMK GdLhGfH GdJQHhjI GdJj JNU GdeQGgb hJTcd HGdfSHI Edjg CgejI cHQi hJbOe dg jO GdYhf hGdeSGYOI HGdEVGaI Edi GdMjGI GdGLJeGYjI ddeQGgb hGdMjGI GdCSQjI(B. (3hGdefgL GdeYJeO aj GdHMK gh efgL hUaj JMdjdj jbhe Ydi hUa MGdI GdeQGgb hMGdI GdehLg GdJQHhj hGdYdGbI HjfgeG hGdCKQ GdfGJL Ydi CSQI GdeQGgb(B.s
(3GdfhY (B: (3cJGHs
Keywords: Adolescents; Adolescents; Orientation et Conseil; School guidance and counseling; (3GdJhLjg hGdEQTGO GdeOQSjs; (3GdeQGgbhfs